Coal Mining Company Responsibility for Environmental Damage in East Barito District, Central Kalimantan - Dedy Dedy; Bambang S. Lautt; Tonich Tonich; Suriansyah Murhaini; Heriamariaty Heriamariaty (Focus Journal : Law Review, 2025)
Coal mining in Barito Timur Regency, Central Kalimantan, significantly contributes to the economy but also negatively impacts the environment. Mining activities have caused water pollution, landscape changes, land degradation, and disruptions to the surrounding communities. This study aims to analyze the accountability of coal mining companies for environmental damage based on criminal, civil, and administrative law aspects. The research employs a qualitative approach with a descriptive case study method. The findings indicate that regulations concerning corporate accountability are outlined in various legal frameworks, such as Law Number 32 of 2009 on Environmental Protection and Management and Law Number 3 of 2020 on Mineral and Coal Mining. Criminal liability allows companies and their management to be prosecuted for violations. Meanwhile, civil liability requires companies to compensate for damages and restore affected environments, while administrative liability includes sanctions such as warnings, fines, and business license revocations. Despite the existing regulations, law enforcement implementation remains weak due to insufficient supervision and corporate non-compliance. Therefore, enhanced government oversight and active community participation are necessary to ensure adherence to environmental regulations. With appropriate measures, a balance between resource exploitation and environmental preservation can be achieved, ensuring ecosystem sustainability and community well-being.